Chemical Composition of the Essential Oil of Two Tanacetum Species from Iran - Mohammad-Bagher Rezaee (Journal of Medicinal Plants and By-products, 2015)
The genus Tanacetum L. is one of the most important medicinal plant that contains 28 species in Iran, 12 of them are endemics. This paper reports the essential oil composition of Tanacetum hololeucum (Bornm.) Podlech; Tanacetum kotschyi (Boiss.) Grierson, growing wild in Iran. Plant flowers were collected from different zones of Dizin in north of Iran. All samples were hydro-distilled (Clevenger apparatus), to produce the oils in T. hololeucum from three zones with yields of (0.35%, 0.35% and 0.16%), and also T. kotschyi, from three zones with yields of (0.57%, 0.41% and 0.10%), respectively. All samples were injected to GC and GC/MS. Main components for T.hololeucum from Dizin of three places from zone 1 were borneol 39.4%, trans- sabinene hydrate 8.4%, 1,8-cineole 8.1%, and from zone 2 were n-hexadecane 14%,  elemol acetate 13.6%, trans-thujone 13.4%,  and from zone 3  were terpinolene 35.7%,  α- phellandrene 23%, γ- eudesmol 7.1% , and in T. kotschyi   also from Dizin of three places from zone 1 were 1,8-cineole 27.8%, terpinolene 13%, trans-thujone 7.2%, and from zone  2  were n-undecane 27.9%, n-hexadecane 14.7%, n-nonadecane 8.7% , and from zone 3 were n-tridecane 55.1%, terpinolene 13.4%, myrcene 7%, respectively.